Opportunities of Traditional Power Structures in Resolving Property Inheritance Conflicts in Meru County - Gakii, Mbaabu Esther; Were, Edmond; Onkware, Kennedy (International Journal For Research In Educational Studies, 2018)
Conflicts over inheritance of property in Africa continue to be resolved by both the conventional judicial systems and the traditional power structures. These traditional structures are the customary decision making organs in the society whose authority originates from the ancestors and is believed to be divine. Their decisions therefore, cannot be questioned or changed. The study therefore, sought to analyze opportunities of traditional power structures in resolving property inheritance conflicts in Meru County, Kenya. This study used a descriptive survey research design to analyze opportunities of traditional power structures in resolving property inheritance conflicts in Meru County, Kenya. Both qualitative and quantitative data was collected. The target population comprised Njuri Ncheke elders who participated in resolving inheritance related conflicts and Njuri Ncheke leaders who were the key informants. To select participants for this study, purposive sampling was used. The sample size comprised all the 54 Njuri Ncheke committee members who included the chairperson, the secretary, and the treasurer from all the 18 Njuri Ncheke Centres in Tigania East. It also included 180 elders of Njuri Ncheke who were involved in resolving inheritance conflict cases in Tigania East and 42 heads of households whose inheritance conflict cases were resolved by Njuri Ncheke. Data collection was done through in-depth and key informant interviews, Focus Group Discussions (FGDs), and direct observation. Data was coded and analyzed according to themes emanating from the narratives. The study revealed that Njuri Ncheke as a traditional institution that offers inheritance conflict resolution has inherent opportunities that for alternative conflict resolution in Tigania East. The key finding was that Njuri Ncheke is not a corrupt but a fair institution in regard to resolution of conflict on property inheritance. The study recommended that Njuri Ncheke elders be used in the fight against corruption at local, national, and international level.